Inhibitory Effect of Sauchinone on UDP-Glucuronosyltransferase (UGT) 2B7 Activity - Byoung Hoon You; Eun Chae Gong; Young Hee Choi (Molecules, 2018)
Herb–drug interaction (HDI) limits clinical application of herbs and drugs, and inhibition of herbs towards uridine diphosphate (UDP)-glucuronosyltransferases (UGTs) has gained attention as one of the important reasons to cause HDIs. Sauchinone, an active lignan isolated from aerial parts of Saururus chinensis (Saururacease), possesses anti-oxidant, anti-inflammatory, and anti-viral activities. In pharmacokinetics of sauchinone, sauchinone is highly distributed to the liver, forming extensive metabolites of sauchinone via UGTs in the liver. Thus, we investigated whether sauchinone inhibited UGTs to explore potential of sauchinone–drug interactions. In human liver microsomes (HLMs), sauchinone inhibited activities of UGT1A1, 1A3, 1A6, and 2B7 with IC50 values of 8.83, 43.9, 0.758, and 0.279 μM, respectively. Sauchinone also noncompetitively inhibited UGT1A6 and 2B7 with Ki values of 1.08 and 0.524 μM, respectively. In in vivo interaction study using mice, sauchinone inhibited UGT2B7-mediated zidovudine metabolism, resulting in increased systemic exposure of zidovudine when sauchinone and zidovudine were co-administered together. Our results indicated that there is potential HDI between sauchinone and drugs undergoing UGT2B7-mediated metabolism, possibly contributing to the safe use of sauchinone and drug combinations.